Hydrazone-schiff base derivatives of 4-(tert-butyl)benzoic acid as potent enzyme inhibitors: In vitro α-amylase, α-glucosidase, tyrosinase inhibition and computational studies - Imen Zghab; Sajjad Ahmad; Imtiaz Ahmad; Aftab Alam; Shah Mulk; Zainab Aziz; Masroor Kamal; Ferjeni Zouidi; Abdulrahman S. Alharbi; Ahmed A. Elhenawy; Momin Khan (PLoS ONE, 2026)
Compounds containing an azomethine functional group are well recognized for their enzyme inhibitory potential. In this study, a series of hydrazone-Schiff base derivatives from 4-(tert-butyl)benzoic acid was synthesized and evaluated for their inhibitory activity against α-amylase, α-glucosidase, and tyrosinase. assays demonstrated pronounced multi-target inhibition. Against α-amylase, compound 2l , bearing a para-nitro substituent, exhibited strong activity with an IC 50 of 2.72 ± 0.09 µM, significantly outperforming the reference acarbose (IC 50 = 16.06 ± 0.05 µM; p < 0.001). Similarly, compound 2l showed potent α-glucosidase inhibition (IC 50 of 3.96 ± 0.21 µM), which was markedly superior to acarbose (IC 50 = 16.65 ± 0.07 µM; p < 0.001). In the tyrosinase inhibition assay, the dimethoxy-substituted derivative 2r emerged as the most active compound, with an IC 50 of 5.61 ± 0.03 µM, approximately threefold more potent than kojic acid (IC 50 = 15.29 ± 1.04 µM; p < 0.001). Molecular docking studies against α-amylase, α-glucosidase, and tyrosinase (PDB IDs: 3BAJ, 5NN5, and 5M8Q, respectively) revealed favorable binding energies ranging from −5.2 to −5.8 kcal/mol and highlighted key interactions with catalytic residues. Density functional theory (DFT) and molecular electrostatic potential (MEP) analyses provided an electronic basis for the observed structure-activity relationships, indicating that enhanced electrophilicity favors glycosidase inhibition, whereas increased nucleophilicity contributes to tyrosinase inhibition. Overall, these findings identify hydrazone Schiff base derivatives as promising scaffolds for the development of multifunctional enzyme inhibitors, with compounds 2l and 2r representing potential lead candidates for further optimization.